A Moran eigenvector spatial filtering specification of entropy measures. Issue 1 (28th November 2021) - Griffith, Daniel A.; Chun, Yongwan; Hauke, Jan
Abstract: Regional science investigations of geographical disparities in socio‐economic development sometimes utilize entropy, which measures a phenomenon's distributional uniformity across geographical space. Entropy also is widely utilized to measure random phenomenon dispersion, and often used to identify the most probable allocation of a phenomenon in space. Its common formulation is with empirical frequencies, following Shannon. Batty introduces spatial entropy assuming equal probability over space. His specification considers probabilities as fundamentally being spatially independent, which does not hold in most empirical geographical analyses. Hence, an entropy measure can be further modified by controlling extra variation caused by spatial autocorrelation. This paper proposes a Moran eigenvector spatial filtering (MESF) entropy specification that accounts for spatial autocorrelation when modelling georeferenced data. Using eigenvectors from a transformed spatial weights matrix, MESF identifies and isolates spatially autocorrelated components within a georeferenced variable. Coupling it with a non‐normal distribution, such as a binomial or beta probability model, which researchers often employ to describe empirical probabilities, expands its utility. The proposed method is examined with an application to regional income inequality in Poland during 2005–2012. This application demonstrates that accounting for spatial autocorrelation further enhances an entropy measure, showing that the MESF specification provides a flexible method for controlling spatial autocorrelation in an entropy formulation. Resumen: Los estudios de las ciencias regionales sobre las disparidades geográficas en el desarrollo socioeconómico utilizan a veces la entropía, que mide la uniformidad distributiva de un fenómeno en un espacio geográfico. La entropía también se emplea a menudo para medir la dispersión de fenómenos aleatorios, y a menudo se utiliza para identificar la asignación más probable de un fenómeno en el espacio. Su formulación común implica frecuencias empíricas, de acuerdo con Shannon. Batty introduce la entropía espacial que asume una probabilidad igual en el espacio. Su especificación considera que las probabilidades son fundamentalmente independientes desde el punto de vista espacial, lo que no se cumple en la mayoría de los análisis geográficos empíricos. Por lo tanto, una medida de entropía puede modificarse aún más si se controla la variación adicional causada por la autocorrelación espacial. Este artículo propone una especificación de entropía de filtrado espacial mediante vectores propios de Moran (MESF, por sus siglas en inglés) que tiene en cuenta la autocorrelación espacial cuando se modelan datos georreferenciados. MESF usa los vectores propios de una matriz de pesos espaciales transformada para identificar y aislar los componentes autocorrelacionados espacialmente dentro de una variable georreferenciada. Si se acopla a una distribución no normal, como un modelo de probabilidad binomial o beta, empleada a menudo por investigadores para describir las probabilidades empíricas, se amplía su utilidad. El método propuesto se estudia mediante una aplicación sobre la desigualdad regional de ingresos en Polonia entre 2005 y 2012. Esta aplicación demuestra que tener en cuenta la autocorrelación espacial mejora la medición de la entropía, y muestra que la especificación MESF proporciona un método flexible para controlar la autocorrelación espacial en una formulación de entropía. 抄録: 社会経済発展の地理的格差を地域科学的に調査する際には、エントロピーを利用することがあるが、これはある現象の地理的空間における分布の均一性を測定するものである。エントロピーはまた、ランダムな現象の分散を測定するのに広く利用されており、ある現象の空間的分布で最も可能性の高いと考えられるパターンを特定するのによく使用される。その一般的な定式は、Shannonの理論に従った、経験的頻度を用いるものである。Battyは、空間のどこにおいても確率は等しいと仮定して空間エントロピーを導入している。Battyは、確率は基本的に空間的に独立していると考えているが、これはほとんどの地理学的実証分析では当てはまらない。したがって、エントロピーによる測定は、空間的自己相関により生じる余分な変動を制御して、改善することができる。本稿では、地理参照データをモデル化する際の空間的自己相関を考慮する、Moran固有ベクトル空間フィルタリング (Moran eigenvector spatial filtering: MESF)エントロピーの仕様を提案する。改変空間重み行列から得た固有値を用いて、MESFにより地理参照変数内の空間的自己相関の成分を特定し分離する。これを、経験的確率を説明するのによく使用される二項分布またはベータ分布の確率モデルなどの非正規分布と結合させることで、その有用性を拡大する。この方法を2005 2012年のポーランドにおける地域所得不平等に適用して検証する。結果から、空間的自己相関を考慮することがエントロピー測定をさらに強化することが示され、MESFの仕様によりエントロピー定式化において空間的自己相関を制御するフレキシブルな方法が得られることが示される。